Barriers and facilitators to prescribing medicinal cannabis in New Zealand - Chris Wilkins; Marta Rychert; Vinuli Withanarachchie (CSIRO Publishing, 2023)
Introduction The New Zealand Medicinal Cannabis Scheme (NZMCS) was established in April 2020 with the aim of expanding access to quality controlled medicinal cannabis products and developing a domestic medicinal cannabis industry. Yet, two years later, many patients report challenges in utilising the NZMCS, including physicians' reluctance to provide prescriptions for products. Aim To explore the barriers and facilitators to prescribing medicinal cannabis in New Zealand. Methods We conducted semi-structured interviews with 31 New Zealand physicians (general practitioners, specialists, and cannabis clinicians) who had discussed medicinal cannabis with patients in the last 6 months. Results Physicians reported the principal barrier to prescribing medicinal cannabis was the limited clinical evidence to support cannabis therapy. Further barriers included: a perceived lack of knowledge of medicinal cannabis; concerns over professional reputation; social stigma; and the price of products. Conversely, the factors that facilitated cannabis prescribing included patients' and physicians' knowledge of medicinal cannabis; some physicians' desire to avoid patients having to engage with private cannabis clinics; and the timing of prescription requests (ie considering medicinal cannabis after other treatments had been exhausted). Discussion Further clinical research of medicinal cannabis medications, education and training, and information would support physicians to deliver more informed advice to patients and enhance professional confidence with cannabis therapies.